The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s0074-02762012000500005
|View full text |Cite
|
Sign up to set email alerts
|

The significance of the amoebocyte-producing organ in Biomphalaria glabrata

Abstract: In molluscs, internal defence against microorganisms is performed by a single cell type, i.e., the haemocyte or amoebocyte. The origin of these cells in Biomphalaria glabrata was initially thought to be localised within the vasculo-connective tissue. More recently, origin from a single organ, termed the amoebocyte-producing organ (APO), has been postulated based on the occurrence of hyperplasia and mitoses during Schistosoma mansoni infection. The present investigation represents a histological, immuno-histoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Unfortunately, as morphological data on these particular cells are not available, comparison with those obtained herein was not possible. Indeed, the similarities between APO and SK cultures, their anatomical proximity in the Biomphalaria body, and partial hemoblast characteristics presented by SK cells suggest that the SK tissue may participate in hemocyte production [Souza and Andrade, 2012;Pan, 1958]. Despite the previously reported differences between SK and APO cells [Sullivan and Spence, 1999;Andrade, 2006, 2012], bright field microscopy performed here revealed that they are very similar in organ-derived cultures [Barbosa et al, 2006b].…”
Section: Cell Interaction With the Parasitementioning
confidence: 56%
“…Unfortunately, as morphological data on these particular cells are not available, comparison with those obtained herein was not possible. Indeed, the similarities between APO and SK cultures, their anatomical proximity in the Biomphalaria body, and partial hemoblast characteristics presented by SK cells suggest that the SK tissue may participate in hemocyte production [Souza and Andrade, 2012;Pan, 1958]. Despite the previously reported differences between SK and APO cells [Sullivan and Spence, 1999;Andrade, 2006, 2012], bright field microscopy performed here revealed that they are very similar in organ-derived cultures [Barbosa et al, 2006b].…”
Section: Cell Interaction With the Parasitementioning
confidence: 56%
“…Souza and Andrade (2006, 2012) [63, 64] have proposed an alternative function for the APO in B. glabrata , i.e., renal absorption and filtration. This hypothesis is based in part on ultrastructural observations that there are no “transitional forms” between mantle epithelial cells and haemocytes [64], and that the APO “vaguely resembled the juxtaglomerular apparatus” of the vertebrate kidney [63].…”
Section: Gastropod Haematopoiesis and Haemocyte Functionmentioning
confidence: 99%
“…This hypothesis is based in part on ultrastructural observations that there are no “transitional forms” between mantle epithelial cells and haemocytes [64], and that the APO “vaguely resembled the juxtaglomerular apparatus” of the vertebrate kidney [63]. However, although haemocyte progenitor cells have been reported from oyster gill epithelium [21], we are not aware of any reports of mantle epithelial cells differentiating into haemocytes, and, therefore, transitional cells would not be expected.…”
Section: Gastropod Haematopoiesis and Haemocyte Functionmentioning
confidence: 99%
“…For cell counting, 10 µl of the hemolymph was diluted (1:1) in saline buffer (18 g L − 1 D-glucose, 12.2 g L − 1 KCl, 0.6 gL − 1 NaHCo3, 380 mOsm, pH 7.8) [24]. The number of total circulating hemocytes was determined by direct observation in a hemocytometer chamber by phase-contrast optical microscopy [25]. The hemocytes were characterized according to Cavalcanti et al [26].…”
Section: Methodsmentioning
confidence: 99%